Inhibition of Wild Enterobacter Cloacae Biofilm Formation by Nanostructured Graphene- and Hexagonal Boron Nitride-Coated Surfaces (Vol 9 49 2019 - Wilkens-Anwandter, M; Zurob-Guzman, E (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Sin Resumen Disponible